1983
DOI: 10.1113/expphysiol.1983.sp002753
|View full text |Cite
|
Sign up to set email alerts
|

The Density and Distribution of Capillaries Around a Synovial Cavity

Abstract: The interpretation of trans‐synovial fluxes requires a knowledge of the number of capillaries present around the joint cavity, and their depths below the surface of the joint lining. Measurements of capillary numbers, depths and dimensions were therefore carried out by light microscopy on synovial tissue sections from five rabbit knees. In addition the surface area of synovial tissue lining the joint was estimated, and the thickness of the synovium measured. Synovial capillary density was found to be uneven, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 23 publications
2
69
1
Order By: Relevance
“…These studies have reported that vascular density varies with the type of synovium and the most vascular synovium is the areolar type. A high capillary density within 25 ,um of the synovial surface has also been noted in rabbit (Knight and Levick 1983) and human (Wilkinson and Edwards 1989) synovium. The present observations using vascular corrosion cast allowed us to demonstrate a three dimensional distribution pattern of the blood vessels in the Synovial fold.…”
Section: Discussionmentioning
confidence: 93%
“…These studies have reported that vascular density varies with the type of synovium and the most vascular synovium is the areolar type. A high capillary density within 25 ,um of the synovial surface has also been noted in rabbit (Knight and Levick 1983) and human (Wilkinson and Edwards 1989) synovium. The present observations using vascular corrosion cast allowed us to demonstrate a three dimensional distribution pattern of the blood vessels in the Synovial fold.…”
Section: Discussionmentioning
confidence: 93%
“…Since the rate of lymph and interstitial fluid formation is closely coupled to capillary filtration rate in the steady state [24,25], the findings indicate a faster generation of interstitial fluid by capillary filtration in muscle. While differences in the Starling forces may contribute to this, the most obvious explanation is that the numerical density of blood capillaries in skeletal muscle (300-1,000/mm 2 ) is *3 times that in adipose subcutis [26][27][28]. The difference in k and the greater mass of muscle indicates that the subfascial compartment generates most of the lymphatic 'load' (volume per unit time) reaching the axilla.…”
Section: Incidence Of Bcrl and Risk Factorsmentioning
confidence: 99%
“…The vertical depth of the tip was calculated as h ⅐ sin , where was the angle of insertion (ϳ45°) and h the distance advanced obliquely, as read from the micromanipulator scale in micrometers. Since the arithmetic mean thickness of rabbit synovium in the suprapatellar pouch is 16 -19 m, and that of the subsynovium is ϳ100 m (Knight and Levick, 1983;Levick and McDonald, 1989a), measurements taken at tip depths of Ͻ10 m were classified as synovial interstitial pressures and those at 20 -35 m were classified as subsynovial interstitial pressures. The region between 10 and 20 m was ignored due to the uncertainty over tissue type near the synovium/subsynovium boundary during a blind penetration.…”
Section: Interstitial Pressure Measurements By the Servonull Micropipmentioning
confidence: 99%